Sosialisasi Dampak Globalisasi Terhadap Pembentukan Karakter Siswa Sekolah Dasar - Raziska Ibrahimi; Lili Kasmini; Helminsyah Helminsyah; Sofiyan Siregar (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2026)
Globalization has brought rapid changes to various aspects of life, including the character development of elementary school students. Easy access to information through the internet and social media provides positive benefits by broadening students' knowledge; however, it also has the potential to encourage negative behaviors if not accompanied by character strengthening. This community service program aimed to improve students' understanding of the impacts of globalization and the importance of developing positive character as preparation for living in a rapidly changing era. The program was implemented through several stages, including preparation, educational socialization, interactive discussions, educational games, and evaluation using pre-tests and post-tests. The activity was conducted at an elementary school involving 35 fifth-grade students. The materials covered the concept of globalization, its positive and negative impacts, national character values, and strategies for using digital technology wisely. The results showed a significant improvement in students' understanding, as indicated by an increase in the average score from 61.43 on the pre-test to 89.14 on the post-test, representing a 45.10% improvement. In addition, the participants demonstrated high enthusiasm throughout the program and were able to identify behaviors reflecting positive character values, such as discipline, responsibility, honesty, politeness, and patriotism in their daily lives. These findings indicate that educational socialization on globalization can serve as an effective preventive effort to strengthen character development among elementary school students from an early age.